Pengaruh Kualitas Makanan Terhadap Keputusan Pembelian Dengan Word of Mouth Communication Sebagai Variabel Intervening Pada Ayam Goreng Krispi Patriot Tebing Tinggi - Anti, Novi; Siregar, Aisyah; Sofian, Mhd. (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2023)
The objective of this study was to determine the effect of food quality on purchasing decisions, the effect of food quality on word of mouth communication, the effect of word of mouth communication on purchasing decisions, and the effect of food quality on purchasing decisions through word of mouth communication as an intervening variable. This study uses the IBM SPSS Statistics 25 application. The population of this research is the consumers of Patriot Crispy Fried Chicken or the people of Tebing Tinggi who have bought Patriot Crispy Fried Chicken as many as 96 people. From the test results, it was found that food quality has a positive and significant effect on purchase decisions. Food quality also has a positive and significant effect on word of mouth communication. And word of mouth communication has a positive and significant effect on purchase decisions. Meanwhile word of mouth communication cannot mediate the relationship between food quality and purchase decision.